Maternal Age at First Delivery and Risk of Cardiovascular Disease Later in Life. (7th March 2013) - Kharazmi, Elham; Fallah, Mahdi; Luoto, Riitta
Abstract : Background . To elucidate the association between maternal age at first delivery and cardiovascular health in women. Material and Method . A nationally representative survey, comprising 3, 937 Finnish women aged 30–99 years with information on most of the potential cardiovascular disease (CVD) risk factors. Weighting survey analyses and logistic regression were performed. Results . Women who had their first delivery at age 25 or less had about five times higher odds ratio for myocardial infarction (fully adjusted OR: 4.82; 95% CI: 1.39–16.75) and about 2-fold higher odds ratio of arrhythmia (fully adjusted OR: 1.82; 95% CI: 1.13–2.92) compared to those who were 31–35 years at their first delivery. Each one year younger maternal age at first delivery predicted a higher risk of myocardial infarction (age-adjusted OR = 1.12 ; 95% CI: 1.06–1.18), hypertension (age-adjusted OR = 1.05 ; 95% CI: 1.03–1.07), arrhythmia (age-adjusted OR = 1.03; 95% CI: 1.01–1.05), angina pectoris (age-adjusted OR = 1.06; 95% CI: 1.02–1.10), and heart failure (age-adjusted OR = 1.05 ; 95% CI: 1.01–1.10). Conclusion . Maternal earlier age at first delivery is related to subsequent development of CVD, especially myocardial infarction. Our findings suggest a need for additional care and monitoring for CVD and its risk factors in women who had their first delivery at young ages.